Required reading for the disenfranchised freshman eaudiobook - Lee, Kristen R. (Listening Library, 2022)
A striking debut novel about a college freshman grappling with the challenges of attending an elite university with a disturbing racist history, which may not be as distant as it seems. "A searing debut.” –Entertainment Weekly Savannah Howard thought everyone followed the same checklist to get into Wooddale University: Take the hardest classes Get perfect grades Give up a social life to score a full ride to a top school   But now that she’s on campus, it’s clear there’s a different rule book. Take student body president, campus royalty, and racist jerk Lucas Cunningham. It’s no secret money bought his acceptance letter. And he’s not the only one. Savannah tries to keep to head down, but when the statue of the university’s first Black president is vandalized, how can she look away? Someone has to put a stop to the injustice. But will telling the truth about Wooddale’s racist past cost Savannah her own future?   First-time novelist Kristen R. Lee delivers a page-turning, thought-provoking story that exposes racism and hypocrisy on college campuses, and champions those who refuse to let it continue.